ANTESEDEN KEPUASAN KONSUMEN DAN MINAT LOYALITAS PADA TOKO MAHKOTA PEKALONGAN - Nandhasari, Nandhasari; Widiyanto, Ibnu (Faculty of Economics and Business Diponegoro University, 2015)
This study aimed to analyze the influences of product quality, service quality, competitive prices and reputation of the store, on the loyalty intention to the Mahkota Stores Pekalongan using customer satisfaction as an intervening variable.In this research, there are 6 variables, 24 indicators and 8 hypothesis testing research hypotheses. The data imployed 250 respondents. The analysis technique used in this research is Structural Equation Model ( SEM ) with AMOS program versi on 20.0.From 8 hypothesis, all hypothesis are accepted. The results also proved that to loyalty intention, can be specified through customer satisfaction and direct effect independent variable. This implies that product quality, service quality, competitive price, and store reputation play important roles to effect customer satisfaction.